The beginning of chaos for Genesis. (June 2019) - Boyle, Marjorie O'Rourke
This article researches and analyzes the complex and controversial origins of Hermann Gunkel's influential idea of chaos in Gen 1.2. It identifies his declared source, context, usage, and rationale. It then documents the undeclared but important philological, philosophical, and theological history of chaos. It identifies Gunkel's thesis of an uncreated chaos as his tacit rejection of Martin Luther's theology of a created chaos. It details the relevant classical philology and Christian theology involved in Luther's apologetics against Aristotle's eternal universe and for Plato's created universe. It discovers Gunkel's unacknowledged citation of Plato's Timaeus as paradigmatic for his own exegesis of Genesis 1 as 'order from disorder'. It discloses the underlying confrontation of Gunkel's inclusive religio-historical method with Luther's theological exclusion of the ancient pagans and their texts from the divine plan of salvation. It invites a more historically informed reevaluation of chaos in Gen 1.2.